2020
DOI: 10.3390/horticulturae6040098
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Nutrient Acquisition Ranges of Greenhouse Grown CBD (Cannabidiol) Hemp (Cannabis sativa) Cultivars

Abstract: There is a growing interest in the production of hemp for the extraction of cannabidiol (CBD) due to reported therapeutic benefits. Recent policy reform has permitted state hemp pilot programs, including the land grant research institutions, the ability to investigate the potential of growing and harvesting Cannabis sativa plants (≤0.3% tetrahydrocannabinol) for these purposes in the U.S. There are vast gaps of knowledge regarding the fertility requirements of hemp cultivars grown in a horticultural production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…That said, the amount of sulfur in DKW is 8.5 times greater than in MS (Supplemental Table S3). Across 13 CBD hemp cultivars, Kalinowski et al (2020) observed an average leaf sulfur concentration of 0.31%, which is greater than the average of 0.23% measured across 536 nonwoody plant species (Fratte et al, 2021). This relatively high leaf concentration of (and possibly requirement for) sulfur in hemp could explain the greater vigor observed with DKW compared with MS in our study.…”
Section: Discussioncontrasting
confidence: 71%
“…That said, the amount of sulfur in DKW is 8.5 times greater than in MS (Supplemental Table S3). Across 13 CBD hemp cultivars, Kalinowski et al (2020) observed an average leaf sulfur concentration of 0.31%, which is greater than the average of 0.23% measured across 536 nonwoody plant species (Fratte et al, 2021). This relatively high leaf concentration of (and possibly requirement for) sulfur in hemp could explain the greater vigor observed with DKW compared with MS in our study.…”
Section: Discussioncontrasting
confidence: 71%
“…High rates of P can affect the uptake of other ions but increasing P supply resulted in only small differences in the nutrient content of flowers and leaves ( Figure 1 ). The nutrient content of the leaves were within published optimal ranges for all P treatments ( Cockson et al., 2019 ; Landis et al., 2019 ; Kalinowski et al., 2020 ).…”
Section: Resultsmentioning
confidence: 59%
“…At ambient CO 2 (415 ppm), WUE is typically around 3 grams per L ( Bugbee, 2004 ; Langenfeld et al., 2022 ). Using a mass balance approach, assuming an optimal leaf P concentration of 0.4% ( Cockson et al., 2019 ; Landis et al., 2019 ; Kalinowski et al., 2020 ), the theoretical P demand is 12 mg per L at ambient CO 2 . Elevated CO 2 reduces transpiration rate and increases photosynthetic rate ( Morison, 1985 ).…”
Section: Discussionmentioning
confidence: 99%
“…Managing the environmental hazards is paramount to getting the best probabilities of success, higher yields, better quality and higher profits (Straten et al, 2010). It is a common practice to cultivate cannabis in greenhouses (Kalinowski et al, 2020).…”
Section: Introductionmentioning
confidence: 99%